The impact of Cocoa Pod Borer on the livelihood responses of farmers in East Sepik Province, Papua New Guinea - Ndrewou, Alois Chapusu (Curtin University, 2023)
Understanding vulnerabilities, resilience, and adaptive capacities of different groups of people under social, economic and environmental conditions is less understood for many communities in developing countries. This thesis examined coping and adaptation strategies of smallholder migrants and landowner cocoa farmers to the financial shock farmers suffered. Land access was the key determinant in their livelihood decisions. The livelihood decisions each group made were based on the resources they accessible to them.